The Relationship Between Age, Education, Occupation, And Parity With Exclusive Breastfeeding Among Working Mothers - Susanti, Rosa; Dina Mariana Br Maha (Rajaki of Tulip Medika Publisher, 2025)
Exclusive breastfeeding (ASI) is the sole nutrition given to infants from birth to six months, without the inclusion of other foods or drinks except for medication, vitamins, or minerals. It is the first, primary, and best natural nutrition for newborns. This study aims to analyze the relationship between age, education, occupation, and parity in exclusive breastfeeding practices among working mothers. Utilizing a cross-sectional survey design, this study employs univariate and bivariate analyses with Chi-Square tests. Conducted between January and April 2024, the research sampled 50 breastfeeding mothers with children aged six months to two years. The findings indicate significant relationships between age, occupation, and parity with exclusive breastfeeding. Educational interventions on the importance of exclusive breastfeeding and proper breast milk storage are recommended